Progress in aluminium and magnesium matrix composites obtained by spark plasma, microwave and induction sintering - Dudina, Dina V.; Georgarakis, Konstantinos; Olevsky, Eugene A. (Taylor & Francis, 2023)
Aluminium and magnesium matrix composites are attractive lightweight materials with strength surpassing that of the corresponding matrix metals. Recent years have seen extensive research aimed at finding ways to control the structure of metal matrix composites and obtaining materials with new sets of properties. This review aims to show that field-assisted sintering is a promising approach for the powder metallurgy processing of aluminium and magnesium matrix composites. The review focuses on the achievements in the compositional and microstructural design and properties of aluminium and magnesium matrix composites obtained by spark plasma sintering, microwave sintering and induction sintering. Issues related to the process scale-up in the field-assisted sintering technologies are also addressed.
Keywords: metal matrix composites; aluminium; magnesium; alloy; spark plasma sintering; induction sintering; microwave sintering